2016
DOI: 10.4102/sajr.v20i2.1044
|View full text |Cite
|
Sign up to set email alerts
|

Systolic function evaluated with cardiovascular magnetic resonance imaging in HIV-infected patients

Abstract: Background: Of all areas worldwide, sub-Saharan Africa is worst affected by the HIV and/or AIDS epidemic. Cardiovascular manifestations are very common and are a powerful contributor to mortality, but often go undetected. Cardiovascular magnetic resonance (CMR) is the most reliable method of assessing cardiac function and morphology and, with this in mind, we initiated a cross-sectional study comparing CMR-determined morphological and functional parameters in asymptomatic HIV-infected patients who were not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, the association between specific ART regimens and myocardial fibrosis also remains underresearched. Two studies demonstrated higher levels of myocardial fibrosis in ART-naive patients compared with people living with HIV who have an established treatment regimen whereas another found no difference . In meta-regression analysis a significant and graded association between higher CD4 cell counts and lower rates of myocardial fibrosis was observed, consistent with the possibility that better HIV control may reduce myocardial pathology …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, the association between specific ART regimens and myocardial fibrosis also remains underresearched. Two studies demonstrated higher levels of myocardial fibrosis in ART-naive patients compared with people living with HIV who have an established treatment regimen whereas another found no difference . In meta-regression analysis a significant and graded association between higher CD4 cell counts and lower rates of myocardial fibrosis was observed, consistent with the possibility that better HIV control may reduce myocardial pathology …”
Section: Discussionmentioning
confidence: 83%
“…Sixteen studies involving 5107 participants, 3446 of whom were HIV positive and 1661 were HIV negative, evaluated computed tomographic coronary angiography . Another 16 studies involving 1698 participants, 1203 of whom were HIV positive and 495 were HIV negative, evaluated cardiac MR imaging . Ten studies involving 681 participants, 435 of whom were HIV positive and 246 were HIV negative, evaluated vascular PET scans .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation